Transformation Approaches to Mainstream Climate Change, Nutrition, Gender and Youth - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Transformation requires understanding complexity, pushing boundaries, applying a systems lens and daring for visionary possibilities. Transformational approaches are being actively pursued by the International Fund for Agricultural Development (IFAD) alongside the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) to mainstream climate change, nutrition, gender and youth participation for rural transformation.